Fluids Engineering 2004
DOI: 10.1115/imece2004-59335
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Interface Between Newtonian and Non-Newtonian Fluids Inside Annular Eccentric Tubes

Abstract: In this work, flow of two adjacent fluids through annular eccentric tubes is analyzed numerically. This kind of flow is found in cementing processes of oil wells, where the cement paste pushes the drilling mud through annular space between the drilling column and the oil well wall. Both drilling mud and cement paste behave as non-Newtonian fluids, and between then a wash fluid is usually used, to avoid their contamination. The analysis of interface configuration between these fluids helps to determine contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Other than the studies by Tehrani and coworkers, there have been only occasional experimental results reported (e.g. Jakobsen et al 1991;Vefring et al 1997;Dutra et al 2004;Nguyen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Other than the studies by Tehrani and coworkers, there have been only occasional experimental results reported (e.g. Jakobsen et al 1991;Vefring et al 1997;Dutra et al 2004;Nguyen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Dutra et al (27) investigaram numericamente o escoamento de dois fluidos em espaços anulares excêntricos. Os efeitos dos parâmetros reológicos dos fluidos e a excentricidade da geometria na eficiência de deslocamento foram estudados para diferentes vazões de bombeio.…”
Section: Revisão Bibliográficaunclassified